Peran Guru Pendidikan Agama Islam Terhadap Perkembangan Spiritual Peserta Didik - Ratna Sari (IQRO: Journal of Islamic Education, 2018)
This study aims to determine the spiritual development of students in SMP Negeri 12 Palopo, and to determine the role of Islamic religious education teachers in the spiritual development of students in 12 Palopo State Middle School. This research is a qualitative descriptive study, using normative approaches, pedagogical approaches, and psychological approaches. Data sources in this study are primary data and secondary data. Collected with Observation and Documentation Interview techniques. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The results of the study show that: (1) The spiritual development of students in Palopo State 12 Junior High School. In addition to the religious material the teacher also provides the properties of local wisdom, namely the habits that exist in the community that is always emphasized to students so that there is no disconnect between the conditions in the community and what they will face, especially in terms of togetherness, kinship, and discipline. through learning materials and will also involve students in social activities such as raising funds for disaster victims, visiting sick friends or teachers, mourn if there is one teacher, community leader, student and student representative who is experiencing a disaster. The direct and active approach is expected to grow and develop a sense of empathy for the surrounding environment. (2) The role of Islamic religious teachers in the spiritual development of students in SMP Negeri 12 Palopo, namely, as instructors, providing learning materials as well as lecturing practices at school, performing congregational prayers before going home from school. The teacher also controls students in their respective environments by using prayer journal books.